2022
DOI: 10.3389/fped.2022.1007813
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging adjuvant therapies in biliary atresia

Abstract: Following Kasai hepatic portoenterostomy (HPE), most patients with biliary atresia will eventually require liver transplantation due to progressive cirrhosis and liver failure. Preventing liver transplantation, or even delaying eventual liver transplantation, is the key to improving long-term outcomes. This review first examines the commonly used adjuvant therapies in post-HPE biliary atresia and the strength of the evidence supporting these therapies. Next, it examines the evolving frontiers of management thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
2
0
2
Order By: Relevance
“…In alcohol-related acute-on-chronic liver failure, glucocorticoid treatment is recommended based upon improved 28-day mortality 31 . In infants with biliary atresia, glucocorticoid therapy is often utilized for both anti-inflammatory and choleretic effects that may improve the clearance of jaundice—of particular interest for the neonate with active inflammatory and cholestatic IFALD 32 . An intriguing small retrospective cohort study from a single center in China found that late postnatal dexamethasone administration for bronchopulmonary dysplasia in preterm infants was strongly protective against development of parenteral nutrition-associated cholestasis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In alcohol-related acute-on-chronic liver failure, glucocorticoid treatment is recommended based upon improved 28-day mortality 31 . In infants with biliary atresia, glucocorticoid therapy is often utilized for both anti-inflammatory and choleretic effects that may improve the clearance of jaundice—of particular interest for the neonate with active inflammatory and cholestatic IFALD 32 . An intriguing small retrospective cohort study from a single center in China found that late postnatal dexamethasone administration for bronchopulmonary dysplasia in preterm infants was strongly protective against development of parenteral nutrition-associated cholestasis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is crucial for the treatment of biliary atresia. Studies have shown that stool color card and MMP-7 can be used as a tool and biomarker for early screening and diagnosis of BA [ 12 , 21 ]. Our study found the abundance ratio of Klebsiella/Bifidobacterium in BA was significantly different from normal control group, which can be used as a tool for identification of BA.…”
Section: Discussionmentioning
confidence: 99%
“…A icterícia colestática é sempre patológica com valores da bilirrubina direta superiores a 1,0mg/dl e as causas da doença podem ser extra ou intra-hepática com um quadro desafiador de diagnósticos diferenciais (Fligor et al, 2022). Entre as causas extra-hepáticas, Wu et al (2022) alertam para urgência pediátrica da atresia biliar cujo diagnostico tardio após sessenta dias de vida reduz o percentual de êxito na cirurgia de hepatoportoenterostomia de Kasai levando ao transplante hepático infantil e aumento na mortalidade.…”
Section: Introductionunclassified
“…Além da experiência clínica do médico não pode ocorrer atrasos na realização de exames de imagem como colangiografia introperatória (COI), colangiografia retrógrada endoscópica (ERC), ultrassonografia do tipo convencional, com 3D/4D, com contraste (CEUS) e a associada com elastografia por onda de cisalhamento (SWE) (Li e Wang, Nos casos duvidosos do diagnóstico de atresia biliar, métodos invasivos devem ser utilizados para identificação de padrão obstrutivo como a biópsia hepática percutânea e a colangiografia intraoperatória, considerada o padrão ouro para o diagnóstico de AB e com maior risco de morbidade segundoGunda et al (2022). Uma vez realizado o diagnóstico, impreterivelmente antes de dois meses de vida do lactente, tem na portoenterostomia hepática de Kasai (KHPE) a principal opção de tratamento cirúrgico com possibilidade de altas taxas de recanalização de ductos biliares e melhora da icterícia protelando em meses há anos a necessidade de transplante hepático(Liu et al,2024) Fligor et al (2022). esclarecem que após a cirurgia de Kasai a maioria dos pacientes que não conseguiu uma desobstrução biliar efetiva provavelmente vão evoluir com a doença hepática ativa caracterizada por colestase, colangite recidivante, cirrose progressiva, hipertensão portal, insuficiência hepática e malignidade e com menores chances de sobrevida sem a realização de transplante hepático.…”
unclassified